History of the Arabic written tradition. - Brockelmann, Carl, 1868-1956. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2017)
The present English translation reproduces the original German of Carl Brockelmann's Geschichte der Arabischen Litteratur (GAL) as accurately as possible. In the interest of user-friendliness the following emendations have been made in the translation: Personal names are written out in full, except b . for ibn ; Brockelmann's transliteration of Arabic has been adapted to comply with modern standards for English-language publications; modern English equivalents are given for place names, e.g. Damascus, Cairo, Jerusalem, et cetera; several erroneous dates have been corrected, and the page references to the two German editions have been retained in the margin, except in the Supplement volumes, where new references to the first two English volumes have been inserted.